Knowledge, attitudes, and practices towards COVID-19 among residents of Bosnia and Herzegovina during the first stage of COVID-19 outbreak - Šljivo, A.; Kačamaković, M.; Siručić, I.; Mujičić, E.; Džubur Kulenović, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In order to control the spread of COVID-19, prevent the crash of health care system and ensure well-being of its residents, Bosnia and Herzegovina has taken rigorous preventive epidemiological measures in the beginning of the pandemic. Currently the situation has dramatically changed. The aim of this study is to present knowledge, attitudes and practices at the beginning of the outbreak in Bosnia and Herzegovina when the spreading of COVID-19 was well controlled and provide useful information to policymakers at this challenging time.Study design. A cross-sectional study conducted by an online questionnaire-based survey.Methods. This study was conducted by an anonymous online questionnaire based on a Chinese study during the fifth week from the beginning of outbreak of COVID-19 in Bosnia and Herzegovina.Results. In total 1,201 respondents, predominantly female (943 or 78.5%), with a mean age 30.57±11.26, scored very high on the knowledge test with a mean score 9.13±1.90. Being male (β: -0.141, p30 (β: -0.099, p=0.030) were associated with lower knowledge scores, while education level of bachelor’s degree and above (β: 0.092, p=0.003), living in urban environment (β: 0.062, p=0.044) and being a student (β: 0.240, p